Spatiotemporal Assessment of Seasonal Water Quality and Quantity of the Peripheral Rivers of Dhaka City Using Multispectral Satellite Images (Journal of Science and Technology Research, 2026)
Rivers play a pivotal role in the hydrologic cycle, and in Dhaka, a bustling metropolitan  city surrounded by four rivers/khals, rapid population growth has led to adverse effects  on these water bodies. The unplanned urbanization for the growing population has  caused excessive pollution and contamination, turning the rivers into lifeless swamps.  Over time, the land area, water quantity, and quality have steadily decreased. This study  aims to address this gap by utilizing multispectral satellite images with field validation  to perform spatiotemporal assessments of seasonal water bodies extent and quality in  the peripheral rivers of Dhaka city. One of the main objectives of the study is to rank  the peripheral rivers with respect to trophic status indexing. The normalized differential  water indices were used to retrieve the river water bodies of the study area. The  conventional methods of trophic status index with suspended sediment concentration,  chlorophyll a concentration and Secchi disk depth of lake water body were applied in  this study. The study observed that the extent of water bodies was reduced by about  16% due to urbanization or transformation of the rivers into land between 1977 to 2023.  Seasonal water quality parameters showed mostly eutrophic conditions with minor  areas of hyper-eutrophic condition in Turag River. Considering the observed water  quality parameters, the examined rivers are no longer suitable for any purposes such  as drinking, fisheries or even agriculture. The geospatial techniques and field validation  both indicated pollution in all the four water bodies. J. of Sci. and Tech. Res. 6(2): 77-96, 2025